Fine-particulate matter (PM2.5), a risk factor for rat gestational diabetes with altered blood glucose and pancreatic GLUT2 expression. (3rd August 2017) - YI, Liu; Wei, Chen; Fan, Wang
Abstract: Recent studies have shown an intriguing association between air pollution and diabetic risk. This study was to investigate the impact of fine particulate matter (PM2.5) on glucose consequences and pancreas glucose transporter2 (GLUT2) expression in a gestational diabetes mellitus (GDM) rat model. GDM rats were exposed to a low PM2.5 dose during pregnancy. After exposure, interleukin-6 (IL-6) and blood routine tests (BRT) were detected. Pancreas underwent pathologic examination. The levels of pancreatic homogenate glutathione peroxidase (GSH-Px), methane dicarboxylic aldehyde (MDA) and GLUT2 were detected. There were lower maternal body weight gain and fetal weight in the PM2.5 group. Exposure to PM2.5 caused increased absorbed blastocyst number, higher blood mono-nuclear cells (PBMC), platelets and IL-6 levels. The postprandial blood glucose (PBG) was elevated at most time points after exposure. The pancreas of PM2.5 exposed rats revealed periductal inflammation under pathological examination. The pancreatic GSH-Px significantly reduced and MDA increased in exposed group. The pancreatic GLUT2 expression was decreased after PM2.5 exposure. Our study provides direct evidence that PM2.5 exposure can result in pancreatic pathological changes and glycemic consequences in GDM rats. The oxidative response and inflammation are involved in PM2.5 increased risk of pancreatic impairment and glycemic consequences.